An investigation into the core appeals for nation branding to attract and retain talent to enhance a country's competitiveness. Issue 5 (15th October 2018) - Silvanto, Sari; Ryan, Jason
Abstract : Purpose: This study aims to empirically examine the most common appeals recommended for use in nation branding campaigns to attract and retain skilled professionals from abroad to enhance a country's economic competitiveness. To assess this, the authors examine how the image and reputation of a country as a destination and location for talent compare to its actual performance in terms of attracting and retaining skilled professionals. This comparison provides useful insights into the aspects of a country's reputation that matter most for attracting the talent it needs to enhance its competitiveness. Design/methodology/approach: This study uses a multivariate analysis to examine a sample of 122 countries using secondary data from the World Economic Forum, the World Bank, the UNDP and other non-governmental sources, such as the Martin Prosperity Institute at the University of Toronto. It then tests the results using a sample of 35 OECD countries to assess whether they apply to all types of countries equally. Findings: The study finds that the two most important factors for ensuring that a country is maximizing its potential to attract skilled professionals are the availability of employment and the degree of ethnic and cultural diversity within the host country. The most important factor for ensuring that a country is maximizing its potential to retain talent, the study finds, is the availability of employment. This does not mean that other factors do not matter, but employment and diversity are crucial for attracting talent from abroad. Research limitations/implications: The study also tests the overall results of the study by using a smaller sample of 35 OECD countries. It finds that the availability of employment and high levels of GDP per capita (i.e. wealth) is important for attracting and retaining skilled professionals in more industrially developed countries. Originality/value: This paper is one of the few empirical studies to examine nation branding to attract and retain talent from abroad to enhance national competitiveness. Its findings suggest that a multifaceted and holistic framework-based approach to nation branding to attract talent, such as that recommended bySilvanto and Ryan (2014 ), is less likely to work in the short term than an approach which primarily emphasizes employment and diversity.